2011
DOI: 10.1016/j.cell.2011.08.050
|View full text |Cite
|
Sign up to set email alerts
|

Master Transcription Factors Determine Cell-Type-Specific Responses to TGF-β Signaling

Abstract: SUMMARY Transforming growth factor beta (TGF-β) signaling, mediated through the transcription factors Smad2 and Smad3 (Smad2/3), directs different responses in different cell types. Here we report that Smad3 co-occupies the genome with cell-type-specific master transcription factors. Thus, Smad3 occupies the genome with Oct4 in embryonic stem (ES) cells, Myod1 in myotubes, and PU.1 in pro-B cells. We find that these master transcription factors are required for Smad3 occupancy and that TGF-β signaling largely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

32
545
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 534 publications
(580 citation statements)
references
References 69 publications
32
545
2
1
Order By: Relevance
“…For example, although active in many tissues, Hox TFs regulate certain genes specifically in some tissues but not in others (Pearson et al 2005). This is even more pronounced for field-specific selector genes such as scalloped (sd) (Guss et al 2001) or TFs downstream from signaling pathways, most of which are reused throughout development and regulate different genes in different contexts (Barolo and Posakony 2002;Mullen et al 2011;Trompouki et al 2011).…”
mentioning
confidence: 99%
“…For example, although active in many tissues, Hox TFs regulate certain genes specifically in some tissues but not in others (Pearson et al 2005). This is even more pronounced for field-specific selector genes such as scalloped (sd) (Guss et al 2001) or TFs downstream from signaling pathways, most of which are reused throughout development and regulate different genes in different contexts (Barolo and Posakony 2002;Mullen et al 2011;Trompouki et al 2011).…”
mentioning
confidence: 99%
“…The combination of inhibitors in 2i and 3i culture mediums, which act on some specific genes from the Wnt/β‐catenin signaling pathway, promote pluripotency in mESCs through the stabilization of β‐catenin that override the inhibitory effect of Tcf3 on some important pluripotency regulators, such as Oct4 and Nanog 50, 51. The TGF‐β/SMAD signaling pathway maintains self‐renewal in mESC through the BMP/SMAD signalling activation of Id family genes 52, while in hESCs is the Activin/Nodal/SMAD2/3 cascade the one responsible for promoting pluripotency 53. Interestingly, several studies have demonstrated that pluripotency regulators form intricate circuits at the transcriptional level 13, 36, 53, 54, and many of the TFs ( Essrb , Klf4 , Stat3 , Tcf3 ) in these regulatory motifs are downstream effectors of the signaling pathways regulating self‐renewal and differentiation.…”
Section: Pluripotent State Gene Expression Heterogeneity Is Tightly Rmentioning
confidence: 99%
“…The TGF‐β/SMAD signaling pathway maintains self‐renewal in mESC through the BMP/SMAD signalling activation of Id family genes 52, while in hESCs is the Activin/Nodal/SMAD2/3 cascade the one responsible for promoting pluripotency 53. Interestingly, several studies have demonstrated that pluripotency regulators form intricate circuits at the transcriptional level 13, 36, 53, 54, and many of the TFs ( Essrb , Klf4 , Stat3 , Tcf3 ) in these regulatory motifs are downstream effectors of the signaling pathways regulating self‐renewal and differentiation. Although the complete spectrum of signaling pathways regulating pluripotency has not been fully described 55, these results demonstrate the confluence of different environmental signals from the microenvironment for the regulation of pluripotency.…”
Section: Pluripotent State Gene Expression Heterogeneity Is Tightly Rmentioning
confidence: 99%
“…In addition to this canonical TGFb signaling pathway, the TGFb receptor complex converges on several other cellular signaling pathways [22,23]. Recently, ChIP-Seq studies indicate that SMAD3 co-occupies genomic loci with transcription factors that are master regulators of diverse cell types including Oct4 in ES cells, MyoD1 in myotubes and Pu.1 in the B-cell lineage [24] and may explain the cellular context-specific effects of TGFb. TGFb is also known for its regulation of postnatal mammary gland development and for its prominent role to act as a tumor suppressor by preventing mammary epithelial cell proliferation [25].…”
Section: Introductionmentioning
confidence: 99%